Accurate human papillomavirus genotyping by 454 pyrosequencing. (10th April 2013) - Militello, V.; Lavezzo, E.; Costanzi, G.; Franchin, E.; Di Camillo, B.; Toppo, S.; Palù, G.; Barzon, L.; Zupanc, T. A.
Abstract Accurate HPV typing is essential for evaluation and monitoring of HPV vaccines, for second‐line testing in cervical cancer screening, and in epidemiological surveys. In this study, we set up and assessed in clinical samples a new HPV typing method based on 454 next‐generation sequencing (NGS) of HPV L1 amplicons, generated by using a modified PGMY primer set with improved sensitivity for some HPV types that are not targeted by standard PGMY primers. By using a median 12 800‐fold coverage, the NGS method allowed us to correctly identify all high‐risk HPV types, in either single or multiple infections, with a sensitivity of 50 genome equivalents, as demonstrated by testing WHO LabNet EQA sample panels. Analysis of mixtures of HPV16‐ and HPV18‐positive cell lines demonstrated that the NGS method could reproducibly quantify the proportion of each HPV type in multiple infections in a wide dynamic range. Testing of HPV‐positive clinical samples showed that NGS could correctly identify a high number of HPV types in multiple infections. The NGS method was also effective in the analysis of a set of cervical specimens with discordant results at hybrid capture 2 and line probe assays. In conclusion, a new HPV typing method based on 454 pyrosequencing was set up. This method was sensitive, specific, quantitative and precise in both single and multiple infections. It could identify a wide range of HPV types and might potentially discover new HPV types.